Feasibility and Challenges for Sequential Treatments in ALK-Rearranged Non-Small-Cell Lung Cancer - Elsayed, Mei; Bozorgmehr, Farastuk; Kazdal, Daniel; Volckmar, Anna-Lena; Sültmann, Holger; Fischer, Jürgen R.; Kriegsmann, Mark; Stenzinger, Albrecht; Thomas, Michael; Christopoulos, Petros (Frontiers in Oncology, 2021)
Background Anaplastic lymphoma kinase-rearranged non-small-cell lung cancer (ALK+ NSCLC) is a model disease for use of targeted therapies (TKI), which are administered sequentially to maximize patient survival. Methods We retrospectively analyzed the flow of 145 consecutive TKI-treated ALK+ NSCLC patients across therapy lines. Suitable patients that could not receive an available next-line therapy (“attrition”) were determined separately for various treatments, based on the approval status of the respective targeted drugs when each treatment failure occurred in each patient. Results At the time of analysis, 70/144 (49%) evaluable patients were still alive. Attrition rates related to targeted treatments were approximately 25-30% and similar for administration of a second-generation (2G) ALK inhibitor (22%, 17/79) or any subsequent systemic therapy (27%, 27/96) after crizotinib, and for the administration of lorlatinib (27%, 6/22) or any subsequent systemic therapy (25%, 15/61) after any 2G TKI. The rate of chemotherapy implementation was 67% (62/93). Both administration of additional TKI (median overall survival [mOS] 59 vs. 41 months for multiple vs. one TKI lines, logrank p=0.002), and chemotherapy (mOS 41 vs. 16 months, logrank p<0.001) were significantly associated with longer survival. Main reason for patients foregoing any subsequent systemic treatment was rapid clinical deterioration (n=40/43 or 93%) caused by tumor progression. In 2/3 of cases (29/43), death occurred under the first failing therapy, while in 11/43 the treatment was switched, but the patient did not respond, deteriorated further, and died within 8 weeks. Conclusions Despite absence of regulatory obstacles and no requirement for specific acquired mutations, 25-30% of ALK+ NSCLC patients forego subsequent systemic therapy due to rapid clinical deterioration, in several cases (approximately 1/3) associated with an ineffective first next-line choice. These results underline the need for closer patient monitoring and broader profiling in order to support earlier and better directed use of available therapies.